Holographic Materials and Optical Systems 2017
DOI: 10.5772/67293
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Holographic Photoalignment for Twisted Nematic Liquid Crystal Gratings

Abstract: Liquid crystal gratings, in which liquid crystal molecules are periodically aligned, are fabricated by highly efficient and practical one-step holographic photoalignment method using a photocrosslinkable polymer liquid crystal (PCLC). This method is an innovative fabrication technique for liquid crystal grating containing a twisted nematic alignment, which does not require a conventional complex fabrication process. In this chapter, three types of liquid crystal gratings with twisted nematic alignment are fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Photoalignment of polymeric films is utilized to fabricate optical and display devices, where light exposure regulates the molecular reorientation direction of the material. Conventionally, a command surface technique using thin photoalignment layers is applied to uniaxial liquid crystal (LC) alignment to fabricate LC displays and birefringent and optical devices combined with polymerizable LCs. By contrast, the use of photoalignable LC polymers can enable direct fabrication of a photoinduced molecularly oriented structure of the polymeric film by means of linearly polarized (LP) light exposure and, in some cases, thermally stimulated self-organization. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoalignment of polymeric films is utilized to fabricate optical and display devices, where light exposure regulates the molecular reorientation direction of the material. Conventionally, a command surface technique using thin photoalignment layers is applied to uniaxial liquid crystal (LC) alignment to fabricate LC displays and birefringent and optical devices combined with polymerizable LCs. By contrast, the use of photoalignable LC polymers can enable direct fabrication of a photoinduced molecularly oriented structure of the polymeric film by means of linearly polarized (LP) light exposure and, in some cases, thermally stimulated self-organization. , …”
Section: Introductionmentioning
confidence: 99%
“…Many types of photosensitive materials have been explored to investigate photoinduced reorientation based on axis-selective trans–cis–trans photoisomerization of azobenzene-containing materials using LP light. Photoreactive LC polymers containing cinnamate or phenyl benzoate mesogenic side groups exhibit a thermally stimulated photoinduced molecular reorientation, which is initiated by axis-selective photo-cross-linking or photo-Fries rearrangement. Additionally, a new molecular orientation technique for photoinactive LC polymeric films from a free (air) surface using an azobenzene-containing polymer realizes a photoinduced molecular orientation of the inner side of the polymers and precise patterning. Furthermore, Shishido et al have reported that dynamic photopolymerization attains molecularly oriented structures of the LC polymeric films, where the self-organized orientation of the mesogenic side groups occurs at the interface between the monomer and polymer using methacrylate monomers with mesogenic side groups. These molecularly oriented films are applicable to birefringent optical devices and polarization-sensitive and polarization-controlled diffraction gratings when the film contains a periodical molecular orientation structure. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Many types of optical and display devices are fabricated by photoalignment of photosensitive polymeric films. Two techniques have achieved photoalignment. One prepares a thin alignment layer for functional materials such as low-molecular-weight and polymerizable liquid crystals (LCs). The other directly generates a molecularly oriented structure of a photosensitive film, and the photoinduced molecular reorientation produces a large optical anisotropy. ,, In some cases, thermally stimulated photoinduced molecular reorientation occurs when a photoalignable material exhibits LC characteristics based on thermally induced self-organization. , Photoalignable LC polymers with cinnamate- or azobenzene-containing materials often display thermally stimulated photoinduced molecular reorientation. , These polymer films are applicable to birefringent optical devices and polarization-controlled diffraction gratings with a periodic molecular orientation structure. ,, …”
Section: Introductionmentioning
confidence: 99%